Studi Perbandingan Implementasi Kegiatan Ektrakurikuler Antara Sekolah Swasta dan Sekolah Negeri di Jakarta Barat (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the differences in the implementation of extracurricular activities at SDN Tomang 01 Jakarta, a public school, and SD Muhammadiyah 27 Jakarta, a private school. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The focus of the study included aspects of planning, implementation, supporting facilities, obstacles encountered, and achievements achieved through extracurricular activities. The results show that both schools share the same commitment to supporting the development of student potential through extracurricular activities, but there are differences in program variety, facility availability, and funding sources. SD Muhammadiyah 27 has a more diverse range of extracurricular activities, including archery, which is supported by school funding sources and parental participation. Meanwhile, SDN Tomang 01 is more dependent on government support, resulting in relatively limited program variety. These differences have implications for student achievement, with private schools demonstrating success at the national level. The research findings confirm that optimal resource support and extracurricular management play an important role in the development of character and student achievement in elementary schools